2018
DOI: 10.1016/j.cognition.2017.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Expected but omitted stimuli affect crossmodal interaction

Abstract: One of the most important ability of our brain is to integrate input from different sensory modalities to create a coherent representation of the environment. Does expectation affect such multisensory integration? In this paper, we tackled this issue by taking advantage from the crossmodal congruency effect (CCE). Participants made elevation judgments to visual target while ignoring tactile distractors. We manipulated the expectation of the tactile distractor by pairing the tactile stimulus to the index finger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
(84 reference statements)
2
1
0
Order By: Relevance
“…Finally, the association is entirely arbitrary and not driven by an underlying spatiotemporal effect, semantic association, or crossmodal correspondence. This supports previous research suggesting that expectations create predictions about forthcoming sensory events, providing a key mechanism to cope with sensory ambiguity (Costantini et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, the association is entirely arbitrary and not driven by an underlying spatiotemporal effect, semantic association, or crossmodal correspondence. This supports previous research suggesting that expectations create predictions about forthcoming sensory events, providing a key mechanism to cope with sensory ambiguity (Costantini et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…This is a distinction that previous research has not typically made. For example, Gekas et al ( 2015 ) and Van Wanrooij et al ( 2010 ) examined expectation in visual search and audio-visual orienting paradigms respectively, and Costantini et al ( 2018 ) found a visuo-tactile cross congruency effect even when a tactile distractor was expected but omitted. While each of these studies show an effect of expectation on perceptual processes, the expectation itself is purely stimulus driven.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a growing body of evidence suggests that top-down influences in the tasks used here do not just reflect heartbeat beliefs themselves, but their integration into cardiac perception (Körmendi et al, 2021(Körmendi et al, , 2022Ring & Brener, 2018), as proposed by the predictive coding frameworks our work is based on (Barrett & Simmons, 2015;Costantini, 2014;Costantini et al, 2018;Critchley & Garfinkel, 2017;Ferri et al, 2013). Here, several aspects of the present data similarly point to the predicted integration of higher-order beliefs with the cardiac perception itself, rather than an influence of the heartrate beliefs themselves.…”
Section: Disentangling Perceptual From Cognitive Contributionssupporting
confidence: 65%